Non-linear externalities in firm localization - Giulio Bottazzi; Ugo Gragnolati; Fabio Vanni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
This paper presents a model of firm localization allowing for non-linear, quadratic externalities. The model and its numerical estimation procedure manage to disentangle localization externalities from the intrinsic advantages of regions. Moreover, the introduction of a quadratic term can accommodate both more-than-linear positive feedbacks as well as congestion effects. Indeed, if the quadratic term is sufficiently negative, one location can reach the point in which the addition of an extra firm decreases the probability for that same location to further attract other firms. In this sense, the present model does not assume a priori that the localization choices of firms are characterized by positive interdependencies. Rather, the methodology allows to estimate whether or not this is actually the case.
Keywords: C12; C16; C51; R30; 330; Firm localization; Externalities; Non-linearities